Utilization of ‘Counting Box’ Media in Addition and Subtraction Word Problems for First Grade Elementary School Students - Septia, Riris; Sari, Arissona Dia Indah; Bakhtiar, Afakhrul Masub (JMEA : Journal of Mathematics Education and Application, 2024)
This research aims to describe the effect of using counting box media in addition and subtraction story questions on the ability to understand concepts in grade 1 students at UPT SD Negeri 29 Gresik and the obstacles to its use. This study used descriptive qualitative method. Data collection in this research was carried out by interviews with class teachers and class 1 students, observations, concept understanding tests and also documentation. The data was analyzed in 3 stages, namely data reduction, data presentation and drawing conclusions. Testing the validity of the researcher's data uses technical triangulation and source triangulation. The results of this research show that the use of counting box media can have a positive effect on grade 1 elementary school students. The effect can be seen from the results of students' ability tests which have increased compared to before using the counting box media, students' enthusiasm becomes high when learning mathematics using the counting box media. This media also makes it easier for students to solve story problems on addition and subtraction of numbers 1-10. However, there were 2 obstacles experienced by students when using counting box media, including the container for holding objects that was not large enough, the cartoon image used as a marker of the subject's identity in the questions was vulnerable to falling off the glass.